Different Indices of Fetal Growth Predict Bone Size and Volumetric Density at 4 Years Old. - Harvey, N; Mahon, P; Robinson, S; Nisbet, C; Javaid, M; Crozier, S; Inskip, H; Godfrey, K; Arden, N; Dennison, E; Cooper, C (2009)
Abstract We have previously demonstrated that higher birth-weight is associated with greater peak and later life bone mineral, and that maternal body build, diet and lifestyle influence prenatal bone mineral accrual. To examine further prenatal influences on bone health we related ultrasound measures of fetal growth to childhood bone size and density. We derived Z-scores for fetal femur length and abdominal circumference and conditional growth velocity from 19-34 weeks gestation from ultrasound measurements in participants in the Southampton Women's Survey. 380 of the offspring underwent dual-energy X-ray absorptiometry at age 4-years [whole body minus head bone area (BA), bone mineral content (BMC), areal bone mineral density (aBMD) and estimated volumetric BMD (vBMD)]. Volumetric bone mineral density was estimated using BMC adjusted for BA, height and weight. A higher velocity of 19-34 week fetal femur growth was strongly associated with greater childhood skeletal size (BA: r=0.30, p<0.0001) but not with volumetric density (vBMD: r=0.03, p=0.51). Conversely, a higher velocity of 19-34 week fetal abdominal growth was associated with greater childhood volumetric density (vBMD: r=0.15, p=0.004) but not with skeletal size (BA: r=0.06, p=0.21). Both fetal measurements were positively associated with BMC and aBMD, indices influenced by both size and density. The velocity of fetal femur length growth from 19-34 weeks gestation predicted childhood skeletal size at age 4-years whereas the velocity of abdominal growth (a measure of liver volume and adiposity) predicted volumetric density. These results suggest a discordance between influences on skeletal size and volumetric density.